Comparison of the environmental impact of alternative flue gas cleaning systems - Nilsson, Jacob (My University, 2020)
When municipal solid waste is incinerated, there are many pollutants that needs to be removed from the flue gas due to environmental or health-related considerations. To do this, several different technologies can be used. The aim of this study is to investigate these options from an environmental standpoint and compare them to see which has the lowest impacts. An LCA was performed on five different system configurations; dry + wet, dry, wet, wet with H2SO4 recycling, and wet with CaCl2 recycling. The inventory data used to calculate the material requirements and emissions was based on information provided by a Swedish waste incineration facility. The impacts of these five scenarios were then evaluated based on the categories climate change, acidification, respiratory inorganics, ozone depletion and human health effects. The handling of long-term emissions in LCA is also discussed. The results indicate that the direct emissions of the waste incineration facility play a major role in all emissions except ozone depletion. If the CaCl2 recycling can be performed, then that option will have the best environmental impact in all categories. Otherwise, the technology with least environmental impact is a combined system with both dry and wet technologies.
Keywords: Municipal solid waste incineration; air pollution control; acid gas treatment; life cycle assessment; long-term emissions